2017
DOI: 10.25081/jsa.2017.v1.819
|View full text |Cite
|
Sign up to set email alerts
|

Effect of plant density on yield and physiological characteristics of six canola cultivars

Abstract: An experiment was performed in the Seed and Plant Improvement Institute, Karaj, Iran to study the influence of plant densities on physiological traits of six canola cultivars. Treatment conditions included three different plant densities (40, 60, and 80 plants m-2) for triplicates of six canola cultivars, namely, Ahamadi, Opera, Okapi, L72, Karaj1, and Sw102. Results indicated that L72 cultivar exhibited the highest yield at the lowest plant density (40 plants m-2). For all cultivars, both plant densities of 6… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 8 publications
2
5
0
Order By: Relevance
“…Our trial results showed the highest significant (p<0.05) seed yield per plant of 85.2 g at 40 plants m -2 in comparison with other plant populations (Table 6). Similar results was obtained in the study of Nasiri et al (2017). Authors include 6 different oilseed rape genotypes (Ahmadi, Okapi, Opera, L72, Karaj1 and SW102) and found that the seed yield at 60 and 80 plants m -2 in all varieties was significantly reduced compared to the 40 plants m -2 .…”
Section: Discussionsupporting
confidence: 83%
“…Our trial results showed the highest significant (p<0.05) seed yield per plant of 85.2 g at 40 plants m -2 in comparison with other plant populations (Table 6). Similar results was obtained in the study of Nasiri et al (2017). Authors include 6 different oilseed rape genotypes (Ahmadi, Okapi, Opera, L72, Karaj1 and SW102) and found that the seed yield at 60 and 80 plants m -2 in all varieties was significantly reduced compared to the 40 plants m -2 .…”
Section: Discussionsupporting
confidence: 83%
“…Similar result were found by parameters than the treatment without spraying humic acid application. These results agree with (Nasiri et al, 2017).…”
Section: Harvest Index (%)supporting
confidence: 92%
“…The rapeseed (Brassica napus L.) crop contains 40-44% oil and is considered to be one of the most important edible oilseeds (Ashkiani et al, 2020;Cashin et al, 2014;FAO, 2018), being the third annual oil crop in the world after soybean and oil palm (Enjalbert et al, 2013). One of the most critical factors that inhibits the development of the area under cultivation and prevents the successful production of rapeseed in semi-arid regions is moisture deficiency at the end of the growth period (reproductive stage) to which it is very susceptible (Nasiri et al, 2017). Among the various abiotic stresses, drought stress is the most severe, destructive and significant restricting environmental factor for sustainable agricultural production (Ardakani et al, 2009;Davaran Hagh et al, 2016;Pace and Benincasa, 2010;Yuncai and Schmidhalter, 2005).…”
Section: Introductionmentioning
confidence: 99%